Falsifikationismus ohne Festsetzungen - Dierig, Simon (Zeitschrift für philosophische Forschung, 2021)
The aim of this essay is to show that the key innovations of Karl Popper's philosophy of science can be disentangled from the prevailing conventionalism in his main work "The Logic of Scientific Discovery." Popper's falsificationism and his rejection of justification can be detached - from his view that the criterion of demarcation, the basic statements ("Basissätze") and the claim that laws are falsifiable hypotheses are stipulations.